Are severe mitral annular calcification still a contraindication to open surgery?. (3rd October 2022) - Cerillo, A; Petrini, F; Bugetti, M; Iannone, L; De Cillis, P; Paduvakis, J; Marchionni, N; Stefano, P
Abstract: Background: Mitral annular calcifications are considered a contraindication to open mitral valve repair/replacement, being associated with a significant risk of rupture of the atrioventricular groove or prosthesis detachment/paraprosthetic leak. Recently a scoring system has been proposed, to quantify the severity of MAC and predict the success of transcatheter valve in MAC implantation. Objective: We present a series of consecutive patients with MAC undergoing sugical mitral valve replacement in recent years. Patients and methods: 82 consecutive patients with MAC underwent open surgical correction from January 2019 at our centre. This was a complex cohort of patients with a high surgical risk profile (STS 5.3±3.2). The degree of MAC was moderate in 60 and severe in 22. Annular decalcification was required in 16 patients, and patch reconstruction of the AV groove in 4. The main predictor of the need for annular decalcification and reconstruction was the depth of calcium infiltration in the ventricular wall at CT. At intraoperative TEE only one patient had a significant paraprosthetic leak, that was repaired during a second short period of aortic cross-clamping. 30 days mortality was 1.2% (one patient), and 87% of patients were alive and well at one year. Comment: The presence of significant mitral annular calcificaion per se should not be considered a contraindication to open mitral valve surgery. The depth of the calcifications in the ventricular wall, as measured at CT 3D multiplanar reconstructions is the best predictor of the need to decalcify/reconstruct the AV groove. Detailed imaging analysis is crucial for the success of the procedure. Funding Acknowledgement: Type of funding sources: None.